Factors Influencing Demand for Up-Market Condominium in Kuala Lumpur - Abu Zarin, Hasmah (1996)
In recent years, condominium living has gained popularity among Malaysians. Many Malaysians bought condominiums because of the facilities (such as swimming pools) provided by the developers. It has become the mode of living for the country's middle and upper class families. condominium developments have mushroomed in all parts of cities in Malaysia particularly in Kuala Lumpur. Residents can enjoy the convenience of having the facilities at their doorsteps, the abundance of greenery and open space. Demand for up-market condominiums in Kuala Lumpur is not certain and this is a main problem to the developers. Developers are in doubt about which factors and how to rank them before decided to come up with condominium projects. What are the real factors that influence the demand or what are the real factors that attract people to buy condominiums? Once these factors are known, developers can then incorporate them in their development. In this way, developers have the confidence to carry out the condominium development effectively and efficiently.